Short Communications: : Causes and Consequences of Complaints Against Anesthesiologists: A 5-year Retrospective Study - Emir Alavi, Cyrus; Sedighinejad, Abbas; Biazar, Gelareh; Yousefshahi, Fardin; Naderi Nabi, Bahram; Rimaz, Siamak; Rafiee, Elahe; Mirblook, Farimah (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Nowadays, complaints against the medical staff and the demand for physicians’ malpractice compensation are increasing. Anesthesiologists are also faced with medical litigation. Because of the importance of this issue and lack of such a research in Guilan Province, this study was conducted to determine the causes and consequences of complaints against anesthesiologists. This study aimed to reveal the anesthesia malpractice claims and underlying factors of its medico-legal litigations. Methods: This study surveyed all complaints against anesthesiologists from the Medical and Forensic Medicine Organization of Rasht from 2011 to 2015. Results: In this study period, 40 complaints against anesthesiologists were registered. The patients who complained were mostly male (52.5%), married (72.5%), and aged >50 years (62.5%). Of these, 6 medical malpractice were occurred (15%). Death of patients (55%) was the most common cause of complaints and negligence is the highest rate of failure by anesthesiologists (90%). Patients in general surgery wards under general anesthesia in governmental educational hospitals were affected the most; 45% in recovery and 27.5% in ICU sectors. In addition, 15% of all referred anesthesia-related malpractice claims positive legal action. Conclusion: Based on the results, a great concern over the performance of assistants in educational care centers, especially in general surgery ward is recommended. It is also necessary to monitor patient’s status carefully in the recovery room and use experienced personnel in there as well as intensive care units.